Combining airborne thermal infrared images and radium isotopes to study submarine groundwater discharge along the French Mediterranean coastline - Beek, P. (2020)
We investigated submarine groundwater discharge (SGD), an important vector for many chemical elements that may impact the quality of the coastal environment. First, we acquired airborne thermal infrared (TIR) images to detect terrestrial groundwater inputs. Few studies have been conducted on SGD along the French Mediterranean coastline. The terrestrial groundwater spring inputs in La Palme and Salses-Leucate coastal lagoons are in the range (0.04–0.11) m3 s−1, ≤ 2% of the local river inputs. In comparison, total SGD estimates to La Palme lagoon (0.56–1.7 m3 s−1) suggest that the recirculation of lagoon water through the sediment is two orders of magnitude greater than the terrestrial groundwater inputs. This study demonstrates the application of airborne TIR remote sensing for detecting surficial groundwater springs, and the inability of the method to detect deeper, submerged springs.